Regional cerebral blood flow and blood volume in patients with subcortical arteriosclerotic encephalopathy (SAE) - Gückel, Friedemann; Brix, Gunnar; Hennerici, Michael G.; Lucht, Robert; Ueltzhöffer, Christine; Neff, Wolfgang (European radiology, 2007)
The aim of the present study was a detailed analysis of the regional cerebral blood flow and blood volume in patients with subcortical arteriosclerotic encephalopathy (SAE) by means of functional magnetic resonance imaging (MRI). A group of 26 patients with SAE and a group of 16 age-matched healthy volunteers were examined. Using a well-established dynamic susceptibility contrast-enhanced MRI method, the regional cerebral blood flow (rCBF) and blood volume (rCBV) were quantified for each subject in 12 different regions in the brain parenchyma. As compared to healthy volunteers, patients with SAE showed significantly reduced rCBF and rCBV values in white matter regions and in the occipital cortex. Regions containing predominantly grey matter show almost normal rCBF and rCBV values. In conclusion, quantitative analysis of rCBF and rCBV values demonstrates clearly that SAE is a disease that is associated with a reduced microcirculation predominantly in white matter.
Gesehen am 26.03.2021